Submarining sensitivity across varied anthropometry in an autonomous driving system environment. (25th November 2019) - Rawska, Katarzyna; Gepner, Bronislaw; Kulkarni, Shubham; Chastain, Kalle; Zhu, Junjun; Richardson, Rachel; Perez-Rapela, Daniel; Forman, Jason; Kerrigan, Jason R.
Abstract: Objective: Self-driving technology will bring novelty in occupant seating choices and vehicle interior design. Thus, vehicle safety systems may be challenged to protect occupants over a wider range of potential postures and seating choices. This study aims to investigate the effects of occupant size, seat recline, and knee bolster position on submarining risk and injury prediction metrics for reclined occupants in frontal crashes. Methods: Frontal crash finite element (FE) simulations were performed with the 3 simplified Global Human Body Model Consortium (GHBMC) occupant models: small female, midsize male, and large male. Additionally, a detailed GHBMC midsize male model was used to compare with selected simplified cases. For each simulation, parameters including seatback recline angle (0.9°, 10.9°, 20.9°, 30.9°) and knee bolster position relative to the occupant (baseline, close, far, and no knee bolster) were varied. Impacts were simulated with the U.S. New Car Assessment Program 56 km/h frontal crash pulse. Occupant kinematics data were extracted from each simulation in a full-factorial sensitivity study to investigate how changes in anthropometry, seating position, and knee bolster position would affect submarining across all simulated cases. Results: Overall, increasing the occupant-to–knee bolster distance resulted in more submarining cases. The threshold for submarining was also affected by the seat recline angle. The lowest threshold observed occurred with 10.9° of recline with the small female model. Submarining was observed at recline angles at and above 20.9° for the midsize male model and 30° for the large male model. The initial lap belt position, pelvis orientation, and their relationship were good predictors of submarining. Increased lumbar flexion moment was observed with increased seat recline angle as well as occupant-to–knee bolster distance. The detailed GHBMC model was more prone to submarining than the simplified model. Conclusions: Submarining may be a major challenge to overcome for reclined occupants, which may become more prevalent with autonomous driving systems. This study shows that the angle of recline, anthropometric variation, and position of the knee bolster affect the risk of submarining. To our knowledge, this is the first study to computationally evaluate the occupant protection implications of seatback recline for multiple body sizes, postures, and positions relative to the vehicle interior.